Lina Lieparskienė, Arūnas Baltėnas. Vietiniai. Nepaprasta kelionė į Trakų kraštą - Miškinienė, Galina (Slavistica Vilnensis, 2019)
Lina Lieparskienė, Arūnas Baltėnas. Vietiniai. Nepaprasta kelionė į Trakų kraštą. Vilnius, 2019. 263 p. ISBN 978-609-95262-1-8, 978-609-425-245-7.
Keywords: none